Microbiology and technology of fermented foods / Robert W Hutkins - Hutkins, Robert W. (Robert Wayne)
With this second edition of Microbiology and Technology of Fermented Foods, Robert Hutkins brings fresh perspectives and updated content to his exhaustive and engaging text on food fermentations. The text covers all major fermented foods, devoting chapters to fermented dairy, meat, and vegetable products, as well breads, beers, wines, vinegars, and soy foods. These insights are enhanced by detailed explanations of the microbiological and biochemical processes that underpin fermentation, while an account of its fascinating history provides readers with richly contextualizing background knowledge.